(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A new art of modern poetry begins after Independence. So many Indian posts like Dom Moraes, P. Lal, Nissim Ezekiel and Kamala Das laid the foundation of modern era of poetry. Among these writer Nissim Ezekiel called “the father of independence Indian verse in English. he establish himself as a towering figures of Indian English poetry . This paper described theme of Nissim Ezekiel poems like Indian identity, superstitions, Love and maritail relationship in his poems.